Analysis of the effect of immersion rate on the distortion and residual stresses in quenched SAE 5160 steel using FEM - R.D. López-García; F.A. García-Pastor; A. Maldonado-Reyes; M.A. Jimémez-Gómez; J.A. Rodríguez-García (Journal of Materials Research and Technology, 2019)
Distortions and residual stresses are common engineering problems present in thermal processes at high temperatures, not only because they lower the quality of the thermally treated components, but also if these stresses are of sufficient magnitude, may cause cracks and fractures to the material during cooling. This investigation focuses on determining the trustworthiness of a mathematical model used in DEFORM-3D software to evaluate the effect of immersion rate on the mechanical properties, distortion and residual stresses formed during the thermal treatment for hardening of SAE 5160 steel used to make leaf springs. The austenitizing temperature used was 920 °C, austenite grain size (AGS) of 10 ASTM, and different immersion rates were studied. The kinetics of phase transformations were calculated using JMatPro software, and they were validated by quench dilatometry. Results showed that the distribution of distortion and residual stresses could be minimized in certain defined ranges of immersion speeds. Keywords: Residual stresses, Quenching, Modeling, Distortion, Simulation